Scaling Up Romania : A Policymaker’s Toolkit - Kapil, Natasha; Rogers, Juan Douglas; Haley, Christopher David; Ghita, Alexandru Florin; Lu, Zoe Cordelia; Arslan, Can (World Bank, Washington, DC, 2022)
This report is divided into two main parts. Part One examines Romania’s Instruments for Entrepreneurship and contains analysis conducted by the World Bank team. It culminates with recommendations to improve the functionality of the Romania’s policy instruments. Part Two presents Policy Recommendation Notes for consideration as operational elements accompanying Romania’s National Startup Ecosystem Strategy. These could easily serve policymakers preparing Romania’s future science, technology, and innovation (STI) policy mix for the upcoming EU financing perspective. Most of the policy recommendations presented in this report overlap with the Top 12 Interventions identified by the Romania entrepreneurial ecosystem, revealing significant alignment between the analytical findings and the demand for policy by key ecosystem stakeholders. Please see Annex A. Top 12 Interventions Identified by the Romanian Entrepreneurial Ecosystem for an overview of the Top 12 Interventions. At the request of the North-East Regional Development Agency (NE RDA), two additional Policy Recommendations are included within, ‘Scale up through exports’ and ‘Implementing Startup Visas’. The team recommends additional analysis to inform a ‘Transform Public Procurement’ recommendation that improves domestic market access for startups.